2014
DOI: 10.14319/ijcto.0203.7
|View full text |Cite
|
Sign up to set email alerts
|

Dose verification of intensity modulated radiotherapy in head and neck tumors

Abstract: Purpose: To evaluate the agreement between measured and calculated doses for head and neck tumors using different gamma criteria and to establish quality assurance protocol for the delivery of IMRT in The National Cancer Institute in Cairo. Methods: The dose is calculated for 30 patients using CMS Treatment Planning System. The ionization chamber (0.6 cm 3 Farmer type) is used for point dose measurements. The 2D-array (PTW 729) and GafChromic films (EBT2) are used for 2D graphical dose distribution. Four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the dose fluence map comparison of TPS and film, results were found between 87.7% and 95.5%. Elawady et al [18] reported, the agreement between measured with 2D-array and calculated doses for head and neck tumors using gamma criteria of 3% DD, 3 mm DTA and suppressing dose below 10%, the average and standard deviation for local dose of gamma index are 81.70 ± 6.28, while those for maximum dose of gamma index are 92.48 ± 4.60.…”
Section: Resultsmentioning
confidence: 91%
“…In the dose fluence map comparison of TPS and film, results were found between 87.7% and 95.5%. Elawady et al [18] reported, the agreement between measured with 2D-array and calculated doses for head and neck tumors using gamma criteria of 3% DD, 3 mm DTA and suppressing dose below 10%, the average and standard deviation for local dose of gamma index are 81.70 ± 6.28, while those for maximum dose of gamma index are 92.48 ± 4.60.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, a dose < x% was not considered, where x% was the small amount of dose in order to eliminate the influence from the low-dose regions. [35][36][37][38] For all brain IMRT plans delivered by the 6 and 15 MV photon beams, the DD calculated between the TPS and Gafchromic EBT3 film was measured at the isocentre and the 30, 60 and 90% area extended after isocentre, in the selected regions of interest (ROI). We made a condition as accepting criteria for the DD as < 1, <3, <5 and <10% at the isocentre, and 30, 60 and 90% area extended from the isocentre, respectively, for all IMRT plans.…”
Section: Absorbed Ddmentioning
confidence: 99%
“…The detector spacing (center to center) is 1 cm. The dimensions of each detector are 0.5 × 0.5 × 0.5 cm 3 [8].…”
Section: Treatment Planningmentioning
confidence: 99%